2019
DOI: 10.1186/s13690-018-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and anxiety symptoms and associated factors among postnatal women in Enugu-North Senatorial District, South-East Nigeria: a cross-sectional study

Abstract: BackgroundPostnatal depression (PND) and anxiety (PNA) among women are prevalent and impairing health problems, with adverse outcomes for mothers and their infants. This study assessed the prevalence of depression, anxiety and associated factors in a sample of postnatal women.MethodA community-based cross-sectional study was conducted on 270 postpartum women attending public health facilities in the study area. Postnatal depression was measured using the Edinburgh Postnatal Depression Scale (EPDS) and anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 61 publications
6
42
0
1
Order By: Relevance
“…We adjusted for the following factors, previously shown to be associated with postpartum depression: maternal age [24,26], maternal education [44], parity [25,45], wealth status [44,46], marital status [27] and place of birth [47]. We fitted a model during the multivariable analysis using generalized estimating equation for the Poisson family, with a log link while considering the cluster effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted for the following factors, previously shown to be associated with postpartum depression: maternal age [24,26], maternal education [44], parity [25,45], wealth status [44,46], marital status [27] and place of birth [47]. We fitted a model during the multivariable analysis using generalized estimating equation for the Poisson family, with a log link while considering the cluster effect.…”
Section: Resultsmentioning
confidence: 99%
“…Although extensive studies have been conducted on postpartum depression [ 24 29 ], few have focused on women who have experienced a perinatal death [ 14 , 30 32 ]. In our study context, the association between perinatal death and postpartum depression has not been established making this evidence scarce in Northern Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…This study's higher scores may be explained by their design method, setting and timing, which are clearly different from the current study. Another study from Nigeria focusing on depression and anxiety in 270 postnatal women found 25.5% (n=69) of its sample with anxiety assessed using HAD-A (10). This study also found that it was history of depression (AOR = 0.12, 95% (CI 0.02, 0.76), and being a mother aged 15-29 years (AOR = 10.31, 95% (CI 1.13, 94.11) that had a significant effect on the development of anxiety symptoms in women..Our study results however were comparable to Muliira et.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have reported increased levels of acute stress and high levels of anxiety in mothers of preterm infants in NICU (8,9). PPD has received considerable research attention while postnatal anxiety (PNA) has been relatively neglected (10). Depressed and anxious mothers have communication difficulties which have a negative impact on the children and family (11).…”
Section: Introductionmentioning
confidence: 99%
“…18 Selanjutnya, penelitian yang dilakukan di Nigeria juga menyebutkan bahwa tidak ada hubungan yang signifikan antara usia ibu dan pendidikan. 19 Pada faktor risiko ini didapatkan hasil bahwa tidak ada hubungan yang signifikan antara komplikasi persalinan (nilai p=1,000), komplikasi perinatal (nilai p=1, 000), jenis persalinan (nilai p=0,694), dan pemberian ASI (nilai p=0,206) dengan risiko terjadinya depresi postpartum. Penelitian ini berbanding terbalik dengan penelitian di Jepang yang tertulis dalam jurnal milik Mathisen et al (2013) yang menyebutkan bahwa dari 627 ibu yang dengan score EPDS tinggi memiliki hubungan yang signifikan dengan melahirkan prematur dan komplikasi persalinan.…”
Section: Pembahasanunclassified